Internet gaming disorder: The prevalence and associated gaming behavior, anxiety, and depression among 8-12-year-old children of private schools in Salem city, India - Reshma Elizabeth Rajan; Sowndarya Gunasekaran; Vinola Duraisamy; Basil M Mathew; T Mercy Vinolia; Pradeep Daniel Gainneos (Wolters Kluwer Medknow Publications, 2024)
Background: The escalating concern over Internet gaming disorder (IGD) among children underscores the urgency of comprehending its determinants and links to mental health, particularly for interventions targeting school-aged children. Aim: This study aimed to evaluate the prevalence and determinants of IGD and its association with depression, anxiety, and behavior among 8-12-year-old children attending private schools in Salem city. Settings and Design: A cross-sectional study involving 780 children aged 8-12 years from Salem district was conducted. Schools were randomly sampled, and data were collected through a self-administered questionnaire. Materials and Methods: Data were gathered from children without genetic, systemic, or mental disorders and brain trauma. The questionnaire, adapted from Alhamoud M A et al. (2022), encompassed sections on sociodemographic characteristics, gaming behavior, and scales for assessing IGD, depression, and anxiety. Administration occurred during school hours with a 30-35 min completion time. Statistical Analysis Used: Data analysis utilized SPSS v23.0, including descriptive statistics, ANOVA, Chi-square tests for intergroup comparisons, and Pearson's correlation coefficient to determine associations. Results: The prevalence of IGD in Salem district was 1.2%, with higher rates of anxiety and depression observed among older children, particularly males. Conclusions: A positive correlation was evident between IGD, anxiety, and depression. Urgent preventive measures have to be warranted to curb the rising trend of IGD, such as limiting screen time and promoting outdoor activities to enhance children's overall health.